Clinical and laboratory factors related to acute isolated vertigo or dizziness and cerebral infarction. Issue 9 (11th August 2018) - Zuo, Lian; Zhan, Yiqiang; Liu, Feifeng; Chen, Chen; Xu, Luran; Calic, Zeljka; Cordato, Dennis; Cappelen‐Smith, Cecilia; Hu, Yunfeng; Li, Gang
Abstract: Objective: To clarify the relationship of clinical factors with isolated vertigo or dizziness of cerebrovascular origin. Methods: Clinical data of patients admitted in East Hospital from Jan. 2015 to Apr. 2016, whose complaint were acute vertigo or dizziness were retrospectively collected. All patients arrived at the emergency department within 24 hr of symptom onset, had no acute ischemic lesion first CT and NIHSS score of 0. Patients were divided into cerebral infarction group and noncerebral infarction group according to subsequent cerebral imaging results and clinical and laboratory factors related to cerebral infarction were analyzed. Result: 51.6% of patients were female ( n = 141). 46 patients (16.8%) were diagnosed with acute cerebral infarction. Baseline demographic data of the two groups was not significantly different. Univariate analysis found that history of smoking ( p = 0.009), headache ( p = 0.028), unsteadiness ( p = 0.009), neuron specific enolase ( p = 0.001), and vertebral artery abnormalities found on imaging ( p = 0.009) were the significant difference between two groups. Increased neuron specific enolase ( p = 0.005) and an abnormal vertebral artery ( p = 0.044) were significant on multivariate analysis. Conclusions: 16.8% of acute isolated vertigo or dizziness presentations were diagnosed with acute cerebral infarction. Increased serum neuron specific enolase and vertebral artery abnormalities were the strongest indicators of acute cerebral infarction. Abstract : Acute isolated vertigo or dizziness is a common clinical symptom and can be caused by cerebral infarction. Increased serum neuron specific enolase and vertebral artery abnormalities were the strongest indicators of acute cerebral infarction.